1995
DOI: 10.1111/j.1944-9720.1995.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reading “Din in the Head”: Evidence of Involuntary Mental Rehearsal in Second Language Readers

Abstract: The phenomenon of involuntary mental rehearsal of language, or the “Din in the head,” has been considered by researchers as an indicator of second language (L2) acquisition among acquirers. Previous studies have noted that the Din occurs primarily among beginning and intermediate L2 students after the reception of oral input that is comprehensible, but not after reading. It has been argued that this lack of a reported Din is due to the fact that such students typically do very little reading, and that acquirer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The 20 participants for this study included 10 native speakers of Chinese and 10 native speakers of Japanese enrolled in a Midwestern U.S. university. Although this number is not extensive, it is large with respect to the qualitative methodology we are using (as described later in this section) and is in line with other studies that have used a similar methodology (e.g., Anton & DiCamilla, 1999;Block, 1986;Cohen, 1998;McQuillan & Rodrigo, 1995;Roebuck, 1998). Subjects were divided into three groups based on their scores on the Michigan Test of English Language Proficiency (MTELP).…”
Section: Participantssupporting
confidence: 58%
“…The 20 participants for this study included 10 native speakers of Chinese and 10 native speakers of Japanese enrolled in a Midwestern U.S. university. Although this number is not extensive, it is large with respect to the qualitative methodology we are using (as described later in this section) and is in line with other studies that have used a similar methodology (e.g., Anton & DiCamilla, 1999;Block, 1986;Cohen, 1998;McQuillan & Rodrigo, 1995;Roebuck, 1998). Subjects were divided into three groups based on their scores on the Michigan Test of English Language Proficiency (MTELP).…”
Section: Participantssupporting
confidence: 58%
“…I noted that the Din experience correlates with less reluctance to speak the language, but I did not make any hypothesis about a sudden “critical stage” that leads to a “sudden and massive restructuring,” as de Bot claimed (p. 173). de Bot stated that there is no research providing evidence for his interpretation of the Din. There certainly is published research confirming that the predictions made in Krashen (1983) are correct: Bedford (1985), de Guerrero (1987), McQuillan (1996), McQuillan and Rodrigo (1995), Parr and Krashen (1986), and Sevilla (1996).…”
mentioning
confidence: 86%
“…Murphey, who brought up 'the song stuck in my head phenomenon' (SSIMH), suggested that music or song may activate the language acquisition device (LAD) or be a 'strategy of the LAD' [25]. In his discussion, he argues that SSIMH may be linked to other phenomena that have been reported in connection with language learning, such as 'involuntary rehearsal of a FL' or 'Din in the head' [26], during intense exposure to the FL, egocentric language as observed in children [27], [28] and the inner speech that evolves from egocentric speech and has also been called verbal thought [29]. According to Murphey, the song can trigger similar rehearsal of language and aid FL acquisition, because if 'involuntary rehearsal is the humming of the efficient LAD, music and song may initially play an associative facilitating role in engaging and stimulating it' [30].…”
Section: Melodymentioning
confidence: 99%